Expanding certified professional midwife services during the COVID‐19 pandemic. Issue 3 (15th April 2022) - Applebaum, Jeremy
Abstract: Given concerns of coronavirus disease 2019 (COVID‐19) acquisition in health care settings and hospital policies reducing visitors for laboring patients, many pregnant women are increasingly considering planned home births. Several state legislatures are considering increasing access to home births by granting licensure and Medicaid coverage of certified professional midwife (CPM) services. In this commentary, issues surrounding the expansion of CPM services including safety, standardization of care, patient satisfaction, racial and income equity, and an overburdened health care system are discussed. Lawmakers must account for these factors when considering proposals to expand CPM practice and payment during a pandemic.